The financial market effects of the ECB's asset purchase programs - Vivien Lewis; Markus Roth (Deutsche Bundesbank, 2017)
The European Central Bank's asset purchase programs, while intended to stabilize the economy, may have unintended side effects on financial stability. This paper aims at gauging the effects on financial markets, the banking sector, and lending to non-financial firms. Using a structural vector autoregression analysis, we find both in the euro area and in Germany a positive effect on output, while prices do not respond significantly. Asset purchases reduce financial stress, but this beneficial effect is overturned in the medium run. In Germany, implicit firm default rates rise, while loan write-offs by banks decrease. This could point to an avoidance of balance sheet repair in the financial sector.
Keywords: C32; E44; E52; E58; 330; asset purchase programs; balance sheet; monetary policy; central bank; shock identification; VAR